Badiiy hikoyalardan foydalanish orqali ingliz tiliNI o‘rganuvchilarning kommunikativ kompetensiyasini rivojlantirishning samarali yo‘llari - Bisenova А. (SCIENCE and SOCIETY, 2025)
The article describes the effectiveness of using literary stories in the development of communicative competence of English language learners. The research results showed that literary stories serve to expand students’ vocabulary, increase the naturalness of speech, cultural understanding, and trust in communication. Also, through interactive and creative activities, students developed empathy, creativity, and independent thinking.